2006
DOI: 10.1210/jc.2005-0745
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Corticosteroid Replacement and Bone Mineral Density in Adult Women with Classical Congenital Adrenal Hyperplasia

Abstract: Context: Concern has been raised regarding the potential impact of chronic glucocorticoid therapy on the bone mineral density (BMD) of patients with congenital adrenal hyperplasia (CAH).Objective: The purpose of this investigation was to assess the impact of chronic glucocorticoid replacement in adult women with classical CAH. Patients and Design:We used dual energy x-ray absorptiometry to evaluate lumbar spine and whole body BMD in 11 women with saltlosing (SL) CAH and 15 with the simple virilizing form. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 16 publications
(25 reference statements)
2
67
0
12
Order By: Relevance
“…Ohmori et al did not find a direct correlation between BMD, cortisol, and androgens; however, they suggested a possible role of DHEAS increase in counterbalancing the negative bone effects of endogenous hypercortisolism (33). Greater bone loss was also found in women on replacement therapy for 21-hydroxylase deficit and lower androgen levels (34), supporting the hypothesis on the importance of cortisol-to-androgen ratio in BMD maintenance (8,32,35). Finally, a strong correlation was observed between DHEAS and lumbar/femoral BMD values in healthy women (36).…”
Section: Discussionmentioning
confidence: 97%
“…Ohmori et al did not find a direct correlation between BMD, cortisol, and androgens; however, they suggested a possible role of DHEAS increase in counterbalancing the negative bone effects of endogenous hypercortisolism (33). Greater bone loss was also found in women on replacement therapy for 21-hydroxylase deficit and lower androgen levels (34), supporting the hypothesis on the importance of cortisol-to-androgen ratio in BMD maintenance (8,32,35). Finally, a strong correlation was observed between DHEAS and lumbar/femoral BMD values in healthy women (36).…”
Section: Discussionmentioning
confidence: 97%
“…Doses of the various glucocorticoids were converted to growth-retarding cortisol equivalents (1 mg of dexamethasoneZ16 mg of prednisoneZ80 mg of hydrocortisone) (15,16,17). Each year, we summed every daily dose of treatment and divided the total by the corresponding body area to obtain the annual cumulative doses of hydrocortisone (mg/m 2 per year).…”
Section: General Proceduresmentioning
confidence: 99%
“…Some studies reported reduced BMD in all PAI patients (2,3), some only in postmenopausal women (4,5) or only in men (6,7), whereas other studies found no significant differences in BMD in either gender (8,9,10). In CAH patients some studies reported no significant differences in BMD between patients with CAH and controls (10,11,12,13,14,15,16), whereas others found reduced BMD in all or some subpopulations of CAH patients (17,18,19,20,21,22,23,24). Until now all studies in this area have had a crosssectional design.…”
Section: Introductionmentioning
confidence: 98%